Use of grafting to characterize and alleviate hybrid dwarfness in common bean - White, Jeffrey W.; Montes, C.; Mendoza, L.Y. (1992)
Crosses between common bean genotypes from different centres of origin can result in F1 plants with dwarfing that is severe enough to prevent formation of F2 seed. This hybrid dwarfness is controlled by two complementary genes, Dl-1 and Dl-2. The dominant alleles at both loci must be present to cause dwarfing, and an increased dose of either allele increases the severity of the dwarfing. Since dwarfing restricts crossing among gene pools, it holds interests for bean breeding and studies of bean evolution and physiology. Results of grafting studies are described which confirm the previously reported dependance of dwarfing on independent root and shoot effects, and further show that grafting may be used to characterize genotypes for presence of the Dl-1 and Dl-2 alleles and to produce normal shoots in plants which otherwise would have been dwarfed. In the first experiment, two carriers each of Dl-1 and Dl-2 and a non-carrier were grafted reciprocally; of the 25 combinations, only the four combinations of Dl-2-carrying shoots with Dl-1-carrying roots produced dwarfing. In a second experiment, 11 carriers of Dl-1 and 9 of Dl-2 were grafted to Dl-1 roots and Dl-2 shoots. Although most graft combinations where Dl-1 roots were combined with Dl-2 shoots resulted in dwarfed plants, 10 genotypes showed mixed responses or otherwise did not respond as expected. Further experiments confirmed the occurrence of materials giving mixed responses or showing dwarfing irrespective of the graft combination. While grafting has utility as a screening tool, results should be interpreted with caution. There remains a need to determine whether the unexplained results reflect effects of additional alleles or genes affecting the dwarfing response. Grafting was used successfully to obtain normal F1 shoots, and ultimately, to produce F2 seed after two cycles of backcrossing (BC2) for four crosses which otherwise would have given dwarfed plants. Segregation of dwarfed and normal plants in progeny rows of F2 plants derived from the BC2 populations showed 1:3 ratios, this being consistent with the reported inheritance.